ORGANISASI PENDIDIKAN DALAM PERSPEKTIF AL-QUR'AN - ARROYAN, MUHAMMAD; Untung, Slamet; Mustakim, Zaenal (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
Organisation is a fundamental necessity for humanity, helping individuals to achieve shared objectives in various areas, including education. Management serves as an important tool in ensuring that organisations operate effectively and productively. This research discusses the organisation of education from the perspective of the Qur’an, emphasising the significance of a clear structure and division of tasks, as well as adaptability to change. The Qur’an, through the concept of "at-tanzhim," underscores orderliness and regulation in the organisation of education. This study employs a qualitative approach, specifically a literature review methodology, collecting data from exegesis texts and relevant references, and analysing it to draw conclusions. The results indicate that the organisation of Islamic education not only focuses on academic achievements but also on character development. Principles such as trust, justice, and consultation are essential in creating an inclusive and fair educational environment. The implementation of Islamic values in education can shape students' character and optimise the resources available. Thus, educational institutions are expected to respond effectively to existing challenges while remaining steadfast in adhering to Islamic principles.